Skin aging - Puizina-Ivić, Neira (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
There are two main processes that induce skin aging: intrinsic and extrinsic. A stochastic process that implies random cell damage as a result of mutations during metabolic processes due to the production of free radicals is also implicated. Extrinsic aging is caused by environmental factors such as sun exposure, air pollution, smoking, alcohol abuse, and poor nutrition. Intrinsicaging reflects the genetic background and depends on time. Various expressions of intrinsic aging include smooth, thinning skin with exaggerated expression lines. Extrinsically aged skin is characterized by photo damage as wrinkles, pigmented lesions, patchy hypopigmentations, and actinic keratoses. Timely protection including physical and chemical sunscreens, as well as avoiding exposure to intense UV irradiation, is most important. A network of antioxidants such as vitamins E and C, coenzyme Q10, alpha-lipoic acid, glutathione, and others can reduce signs of aging. Further anti-aging productsare three generations of retinoids, among which the first generation is broadly accepted. A diet with lot of fruits and vegetables containing antioxidants is recommended as well as exercise two or three times a week.
Keywords: Alcohol Drinking; Alkohol, pitje; Antioksidanti; antioxidant; Antioxidants; dermatologija; Kajenje; Keratosis; Keratoza; Kisik, aktivne oblike; koža; Koža, staranje; preventiva; Reactive Oxygen Species; Skin Aging; Smoking; staranje kože; Ultravijolični žarki; Ultraviolet Rays